Physico and chemical approach for the processing of waste titanium tetrachloride - Savin, Yu. L.; Prykhodko, O. P.; Savin, L. S. (Science and Transport Progress, 2008)
In the article the studies devoted to a physical-chemical approach on treatment of wastes of titanium tetrachloride production are described. An innovation scheme providing the wasteless titanium production is proposed.